Protocol for the Prognostication of Consciousness Recovery Following a Brain Injury - Duclos, Catherine; Norton, Loretta; Laforge, Geoffrey; Frantz, Allison; Maschke, Charlotte; Badawy, Mohamed; Letourneau, Justin; Slessarev, Marat; Gofton, Teneille; Debicki, Derek; Owen, Adrian M.; Blain-Moraes, Stefanie (Frontiers in Human Neuroscience, 2020)
Individuals who have suffered a severe brain injury typically require extensive hospitalization in intensive care units (ICU), where critical treatment decisions are made to maximize their likelihood of recovering consciousness and cognitive function. These treatment decisions can be difficult when the neurological assessment of the patient is limited by unreliable behavioral responses. Reliable objective and quantifiable markers are lacking and there is both 1) a poor understanding of the mechanisms underlying the brain’s ability to reconstitute consciousness and cognition after an injury and 2) the absence of a reliable and clinically feasible method of tracking cognitive recovery in ICU survivors. Our goal is to develop and validate a clinically relevant EEG paradigm that can inform the prognosis of unresponsive, brain-injured patients in the ICU. This protocol describes a study to develop a point-of-care system intended to accurately predict outcomes of unresponsive, brain-injured patients in the ICU. We will recruit 200 continuously-sedated brain-injured patients across five ICUs. Between 24 hours and seven days post-ICU admission, high-density EEG will be recorded from behaviorally unresponsive patients before, during and after a brief cessation of pharmacological sedation. Once patients have reached the waking stage, they will be asked to complete an abridged Cambridge Brain Sciences battery, a web-based series of neurocognitive tests. The test series will be repeated every day during acute admission (ICU, ward), or as often as possible given the constraints of ICU and ward care. Following discharge, patients will continue to complete the same test series on weekly, and then monthly basis, for up to 12 months following injury. Functional outcomes will also be assessed up to 12 months post-injury. We anticipate our findings will lead to an increased ability to identify patients, as soon as possible after their brain injury, who are most likely to survive, and to make accurate predictions about their long-term cognitive and functional outcome. In addition to providing critically needed support for clinical decision-making, this study has the potential to transform our understanding of key functional EEG networks associated with consciousness and cognition.